Exploring the potential effects of Lactococcus lactis D4 on the proliferation, apoptosis, and inflammatory responses in colorectal cancer cells - Rivai, Muhammad I.; Lusikooy, Ronald E.; Putra, Andani E.; Elliyanti, Aisyah; Sukma, Ade (Narra Sains Indonesia, 2025)
Lactococcus lactis D4 is a probiotic produced through the fermentation of buffalo milk in bamboo, namely